The role of seleniummedications in the treatment of autoimmune thyroiditis - Mykhaylyk, E. A.; Михайлюк, Євгеній Олегович (г. Шымкент: Серпилис, 2016)
Introduction in areas with severe selenium deficiency there is a higher incidence of thyroiditis due to a decreased activity of selenium-dependent glutathione peroxidase activity within thyroid cells. Selenium-dependent enzymes also have several modifying effects on the immune system. Therefore, even mild selenium deficiency may contribute to the development and maintenance of autoimmune thyroid diseases. Research goalto study the effects of selenium medications in the treatment of autoimmune Thyroiditis.
Keywords: тези